New dark species of Cribraria (Myxomycetes) from wetland ecosystem in Tatarstan (Russia) - Sadykov, Ruslan E.; Potapov, Kim O. (Phytotaxa, 2023)
Fruiting bodies of a grey-coloured Cribraria were found in moist chambers on dead wood of Salix from a wetland ecosystem in Kazan (Tatarstan, Russia). Morphological analysis showed that the species, described as Cribraria gothica, probably belongs to a group with C. tenella and C. languescens, but differs in many respects. Most vivid factors are plumbeous colour of sporocysts, small grey spores and creamy-coloured top of stalk. The comparative characteristic and a key to these related species are given.